2007
DOI: 10.1038/sj.jp.7211775
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and cord serum lipid profiles of preterm infants with respiratory distress syndrome

Abstract: Background: Lipid metabolism has an important role in fetal development during the late stage of gestation, including growth and fat accretion in utero, increasing amniotic fluid lecithin levels with maturation of pulmonary function and changes in the levels of minor phospholipids in amniotic fluid.Objective: The aim of this study was to compare the maternal and cord lipid profiles of preterm infants with respiratory distress syndrome (RDS) and a control group without RDS. Method:The study groups consisted of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 16 publications
1
7
0
Order By: Relevance
“…4;6;32-35 While a number of studies have observed a positive association between preterm birth and elevated TNF-α 2;3;28 or preterm birth and indicators of hyperlipidemia, 4;6;35 other studies have observed no such association. 29-31;33;34 In the current study, we observed evidence for such inconsistency as well. For example, whereas in California samples an elevated TNF-α and an elevated TGs:HDL ratio was associated with an increased risk for early preterm birth before consideration of cooccurrence, no such pattern was observed in Iowa samples.…”
Section: Commentsupporting
confidence: 67%
“…4;6;32-35 While a number of studies have observed a positive association between preterm birth and elevated TNF-α 2;3;28 or preterm birth and indicators of hyperlipidemia, 4;6;35 other studies have observed no such association. 29-31;33;34 In the current study, we observed evidence for such inconsistency as well. For example, whereas in California samples an elevated TNF-α and an elevated TGs:HDL ratio was associated with an increased risk for early preterm birth before consideration of cooccurrence, no such pattern was observed in Iowa samples.…”
Section: Commentsupporting
confidence: 67%
“…These changes may be attributed to the maturity of pregnancy and also the nutritional status of the fetus. Earlier study [11] has found a close relationship between pregravid BMI and TG levels of neonates. But in the present study there was a lack of correlation between maternal post-delivery BMI and the neonates' lipid profile.…”
Section: Discussionmentioning
confidence: 68%
“…Cord lipid concentrations have been analyzed in human neonates with respiratory distress syndrome (RDS) [6,7]. Gunes et al [7] reported that total cholesterol (TC), HDL, and LDL cholesterol levels were lower in infants with RDS and in their mothers.…”
Section: Introductionmentioning
confidence: 99%
“…Cord lipid concentrations have been analyzed in human neonates with respiratory distress syndrome (RDS) [6,7]. Gunes et al [7] reported that total cholesterol (TC), HDL, and LDL cholesterol levels were lower in infants with RDS and in their mothers. Lane et al [6], on the other hand, demonstrated elevated TC and TG levels in larger RDS infants with birth weight of 2000 to 2499 g and impaired lipid transport across the placenta in smaller RDS infants.…”
Section: Introductionmentioning
confidence: 99%